SOLUTION OF THE TIME-INDEPENDENT SCHRÖDINGER EQUATION FOR THE ROSEN–MORSE POTENTIAL BY USING THE GALERKIN METHOD - Widagda, I Gusti Agung; Artawan, Nengah; Trisnawati, Ni Luh Putu; Adnyana, I Gusti Agung Putra; Paramarta, Ida Bagus Alit (Universitas Mataram, 2025)
This study presents a numerical solution to the time-independent Schrödinger equation (TISE) for the Rosen-Morse potential using the Galerkin method. The Rosen-Morse potential, commonly used in atomic and molecular physics, has known analytical solutions under certain conditions. By transforming the TISE into a Jacobi differential equation, the analytical wave function and energy levels can be derived. However, analytical solutions are limited to ideal cases, highlighting the need for numerical methods in more general scenarios. The Galerkin method is implemented by expanding the wave function using Sine basis functions and projecting the TISE onto this basis. The resulting eigenvalue problem is solved by constructing the Hamiltonian matrix from kinetic and potential energy operators. Numerical results from the Galerkin method are compared with analytical solutions using graphical analysis, percentage error (% error), and statistical tests, including the Mann-Whitney U test. The results demonstrate that the probability densities obtained using the Galerkin method closely approximate the analytical solution. This is visually evident from the overlapping of probability density plots from both methods. The percentage error of the probability densities is below 1 %, entirely. Furthermore, the Mann–Whitney U test yields a p-value less than 0.05, indicating that the differences between the two sets of probability densities are statistically insignificant at the 95% confidence level. These findings highlight the Galerkin method’s effectiveness and accuracy as a robust numerical tool for solving the TISE with the Rosen-Morse potential.